The Role of Teachers in Implementing Inclusive Education for Children with Special Needs in General School Enviroments - Afriani, Gusma (Global Education Journal, 2025)
Inclusive education has become a global priority to ensure equal learning opportunities for all students, including children with special needs. However, in many general school environments, the implementation of inclusive education remains a significant challenge, particularly due to the limited readiness of teachers. This study aims to explore the role of teachers in implementing inclusive education for children with special needs in general school settings. A qualitative descriptive approach was employed, involving semi-structured interviews, classroom observations, and document analysis at three inclusive public primary schools in [Insert Location]. The data were analyzed using Miles and Huberman's interactive model, focusing on teachers' strategies, challenges, and institutional support. The findings reveal that while teachers generally have positive attitudes toward inclusion, many feel unprepared due to insufficient training and lack of resources. Teachers apply adaptive strategies, but systemic constraints, including limited collaboration and negative societal attitudes, hinder effective implementation. The study concludes that teachers play a pivotal yet constrained role in fostering inclusion, highlighting the need for enhanced training, structural support, and cultural change within schools. This research contributes to understanding the practical realities of inclusive education and offers insights for policymakers, school leaders, and teacher development programs.